2020
DOI: 10.1097/bpo.0000000000001708
|View full text |Cite
|
Sign up to set email alerts
|

Can Chiari Osteotomy Favorably Influence Long-term Hip Degradation in Multiple Epiphyseal Dysplasia and Pseudoachondroplasia?

Abstract: Background: Multiple epiphyseal dysplasia (MED) and pseudoachondroplasia (PSACH) are congenital skeletal disorders characterized by irregular epiphyses, mild or severe short stature and early-onset osteoarthritis which frequently affect the hips. The current study evaluates the long-term results of the Chiari osteotomy in MED and PSACH patients. Methods: Twenty patients (14 MED and 6 PSACH) were retrospectively included. Clinical assessment used the Pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Andrzejewski et al . [20] evaluated the efficacy of Chiari osteotomy in MED and PSACH patients. This study had an average of 20-year follow-up on 20 patients (14 MED) and found the PMA score improved from 12.7 preoperatively to 15.2 postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Andrzejewski et al . [20] evaluated the efficacy of Chiari osteotomy in MED and PSACH patients. This study had an average of 20-year follow-up on 20 patients (14 MED) and found the PMA score improved from 12.7 preoperatively to 15.2 postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…To delay the onset of premature osteoarthritis, various osteotomies have been indicated for correcting deformities. 5 , 6 ) Growth modulation procedures through hemiepiphysiodesis were also employed at the growth plates of the distal femur and proximal tibia in patients before skeletal maturity. 21 ) However, the long-term results of these realignment procedures remain unproven.…”
Section: Discussionmentioning
confidence: 99%
“… 4 ) To prevent early osteoarthritis, some patients undergo osteotomy to realign the lower extremities. 5 , 6 ) In addition to early osteoarthritis, MED is characterized by a disproportionate short stature. 7 ) As well as premature osteoarthritis, orthopedic problems in SED include disproportionate short stature, scoliosis, odontoid hypoplasia, and atlantoaxial instability.…”
Section: Introductionmentioning
confidence: 99%
“…Femoral and pelvic osteotomies are also performed in patients who have sequelae of developmental dysplasia of the hip, sequelae of septic arthritis of the hip, Legg-Calvé-Perthes disease, in skeletal dysplasia etc. (5,6,7).…”
Section: Introductionmentioning
confidence: 99%